The concept of post-truth in the media space and political nature - Yessimova, Г.А.; Yertassova, Г.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The article is devoted to the analysis of the phenomenon of post-truth in modern political communication. In the era of the information society, with the development of digital technologies, it is becoming more difficult to distinguish truth from lies every day. Therefore, the concept of Post-truth or "post-truth" has emerged as the most important characteristic of the modern media space and political discourse.The article analyzes the essence, etymology of the concept of Post-truth in the media space, the causes of its occurrence and political characteristics. The conclusions of Western, Russian, and Kazakh scientists are analyzed, and approaches to preventing the negative impact of the post-truth era are considered. Through real-life examples, it is proved that the lack of censorship on the Internet leads to an increase in the number of false messages distributed at different levels, and the role of facts, evidence, theoretical foundations and critical thinking in the post-truth era is also studied. In conclusion, the authors note that populist leaders often appear in the post-truth political space, who make false promises to achieve their interests and use rhetoric aimed at manipulating voters' emotions and mass media become platforms for political manipulation.